Complications in right‐sided paraaortic lymphadenectomy: ventral tributaries of the inferior vena cava. Issue 1 (21st May 2013) - Turyna, Radovan; Kachlik, David; Kucera, Eduard; Kujal, Petr; Feyereisl, Jaroslav; Baca, Vaclav
Abstract The purpose of this study was to describe the distribution and structure of ventral tributaries leading into the inferior vena cava where right‐sided paraaortic lymphadenectomy is performed. The study examined 21 retroperitoneal specimens by graphic reconstruction, statistical evaluation, and histological examination of ventral tributaries (VTs). Seventy VTs were identified. The average number per specimen was 3.33. There were 20, 40, and 40% of VTs found in Levels I, II, and III, respectively. During the preparation, we observed an unusual arrangement of the IVC wall, into which VTs were led through a preformed sleeve‐like channel and anchored near the lumen. This finding is a key mechanism that explains the ease with which VTs are extracted during surgery. Knowledge of the distribution and histological structure of VTs allows proper orientation of the retroperitoneal area of the front wall of inferior vena cava, which is essential for uncomplicated right‐sided paraaortic lymphadenectomy. The histological structure of the VT ostium within the wall of the inferior vena cava explains why injury is easy during the procedure.